Remodeling of outlets in three pilot distributaries under the Farmer Managed Irrigation Project in Sindh Province, Pakistan - Lashari, Bakhshal K.; Murray-Rust, Hammond (International Water Management Institute, 2000)
Addresses remodeling of outlets to achieve equitable water distribution where studies have shown considerable inequity. Recommendations are made for the implementation of remodeling that involve the farmer organizations. This process is to be undertaken jointly with the area water board staff.